The Training of Rhythm Skills and Executive Function: A Systematic Review - J. Riikka Ahokas; Suvi Saarikallio; Graham Welch; Usha Goswami; Tiina Parviainen (Music & Science)
Objective The focus of this study is on rhythm-elicited movement and its impacts on executive function. The main aim of this review was to identify previous, controlled intervention research on this topic, and to study the effectiveness of the included research interventions. We hypothesized we would find research supporting the alleged positive impact of rhythm training on cognition. Methods Systematic literature searches were performed in Web of Science (WoS), PubMed, Education Resources Information Center (ERIC), and APA PsycArticles and PsycInfo databases from 2000 to May 2022. The selected studies were evaluated for methodological quality using the modified Downs and Black checklist. Results The eligibility criteria of this review identified populations from preschool to old age and included research interventions that could be defined as “training music rhythm skills”. Only studies with active control training using executive function (EF) measures, published between 2000 and 2022, peer reviewed, and written in English were included. From the initial result of a total of 15,677 identified records, 10 research reports met the eligibility criteria and were included in the final synthesis of this systematic review. The mean methodological quality score of these records was 24.7 out of 28 on the Downs and Black checklist. Five of the included studies provided statistically significant results in regard to our hypothesis. Conclusion During our targeted review period of 2000–2022, there is a fundamental paucity of studies aiming at testing the benefits of rhythm training on EF.